Alternating Array Stacking of Ag26Au and Ag24Au Nanoclusters. (21st June 2019) - He, Lizhong; Gan, Zibao; Xia, Nan; Liao, Lingwen; Wu, Zhikun
Abstract: An assembly strategy for metal nanoclusters using electrostatic interactions with weak interactions, such as C−H⋅⋅⋅π and π⋅⋅⋅π interactions in which cationic [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + and anionic [Ag24 Au(2‐EBT)18 ] − nanoclusters gather and assemble in an unusual alternating array stacking structure is presented. [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + [Ag24 Au(2‐EBT)18 ] − is a new compound type, a double nanocluster ion compound (DNIC). A single nanocluster ion compound (SNIC) [PPh4 ] + [Ag24 Au(2‐EBT)18 ] − was also synthesized, having a k‐vector‐differential crystallographic arrangement. [PPh4 ] + [Ag24 Au(2, 4‐DMBT)18 ] − adopts a different assembly mode from both [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + [Ag24 Au(2‐EBT)18 ] − and [PPh4 ] + [Ag24 Au(2‐EBT)18 ] − . Thus, the striking packing differences of [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + [Ag24 Au(2‐EBT)18 ] −, [PPh4 ] + [Ag24 Au(2‐EBT)18 ] − and the existing [PPh4 ] + [Ag24 Au(2, 4‐DMBT)18 ] − from each other indicate the notable influence of ligands and counterions on the self‐assembly of nanoclusters. Abstract : DNIC und SNIC : Eine ionische Doppelnanocluster‐Verbindung (DNIC) wurde synthetisiert, die eine einzigartige alternierende Stapelanordnung der kationischen und anionischen Nanocluster aufweist. Eine Verbindung mit nur einem Nanocluster (SNIC) wurde ebenfalls erhalten. Die Packungsunterschiede zwischen DNIC und SNIC sind ein Hinweis auf den großen Einfluss von Liganden und Gegenionen auf die kristallographische Anordnung.